The next evangelicalism : releasing the church from Western cultural captivity - Rah, Soong-Chan. (Downers Grove, Ill. : IVP Books, 2009)
Soong-Chan Rah calls the North American church to escape its captivity to Western cultural trappings and to embrace a new evangelicalism that is diverse and multiethnic. Rah brings keen analysis to the limitations of American Christianity and shows how captivity to Western individualism and materialism has played itself out in megachurches and emergent churches alike. --from publisher description
Individualism : the heartbeat of Western, white cultural captivity -- Consumerism and materialism : the soul of Western, white cultural captivity -- Racism : the residue of Western, white cultural captivity -- The Church growth movement and megachurches -- The emergent church's captivity to Western, white culture -- The cultural imperialism of the Western, white captivity of the church -- Suffering and celebration : learning from the African American and Native American communities -- Holistic evangelism : learning from the immigrant church -- A multicultural worldview : learning from the second generation.
Includes bibliographical references (pages [209]-226) and indexes.
Description based on print version record.
Keywords: Evangelicalism -- History -- 21st century; Church history -- 21st century; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books